Pinecone 1961 - Valdosta State College (Valdosta State College, 1961)
By a special Act of Legislature the college was established in 1906. It was first known as South Georgia State Normal College, and in 1923 it was changed to Georgia State Womans College . . . Later in 1950 the name was changed to the present Valdosta State College . . . And so it is as the old makes way for the new and in turn the new looks toward the future. May we ever press forward with the determination to reach our goals . . . Let us keep in mind these very wise words from Alexander Pope, "Be not the last by which the new is tried, nor the first to lay the old aside."
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; University History; Americana